PREPARATION AND CRYSTAL STRUCTURE OF CaCl .[OC(NH ) ] (Journal of Sciences, Islamic Republic of Iran)
Calcium dichloride tetra urea was prepared by the reaction of calcium chloride with urea in aqueous solution. The crystals are monoclinic, a= 7.633, b= 12.45 1, c= 8.118 ?,? = 113.17, Z = 4, space group P 2,/a. The crystal structure was determined by single crystal X-ray methods and refined to R= 0.041. The calcium atoms are coordinated to four oxygen atoms of urea and to two chloride ions. The coordination polyhedra are distorted octahedral